Dietary Hermetia illucens Larvae Replacement Alleviates Diarrhea and Improves Intestinal Barrier Function in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Jin, Xinxin; Yuan, Boyu; Liu, Mingming; Zhu, Mingqiang; Zhang, Xue; Xie, Gaijie; Wu, Wenxiang; Wang, Zifan; Xu, Haidong; Lv, Yantao; Huang, Yanhua; Wang, Wei (Frontiers in Veterinary Science, 2021)
A high-quality protein substitute, Hermetia illucens (black soldier fly) larvae powder, is rich in protein and often used in animal feed. This study aimed to investigate the feasibility and optimal ratio of replacing fish meal with H. illucens larvae in weaned piglets and to demonstrate the effects on piglets' growth performance, intestinal microflora and immune performance. Forty-eight female weaned piglets were randomly classified into three groups. Each group consisted of eight pens (replicates), with two piglets per pen. Three groups containing different proportions of H. illucens larvae (0, 4, and 8%) were referred to as C, HI4, and HI8. We first designed a 28-day feeding experiment to detect growth performance; after that, the piglets were induced with oral gavage of enterotoxigenic Escherichia coli K88 (ETEC K88) and recording diarrhea on day 29 of the experiment. Samples were taken on the 32nd day to detect the effect of H. illucens larvae on the immune performance of the weaned piglets. H. illucens larvae replacement did not cause any obvious change in the growth performance nether in HI4 nor in HI8 of weaned piglets with 28 d feeding stage. H. illucens larvae could improve the intestinal health of weaned piglets by increasing the content of Lactobacillus and reducing the content of Streptococcus. Compared with C+K88 group, the diarrhea rate was attenuated for the H. illucens supplemented group. The integrity of ileum villi in HI4+K88 and HI8+K88 groups was better than that in C+K88 group, and the villi in C+K88 group were severely damaged. The expression of IL-10, Occludin and Claudin-3 in the intestinal mucosa of the HI4+K88 group and HI8+K88 group were significantly increased (P < 0.05), and the expression of TNF-α was significantly decreased (P < 0.05) compared with the C+K88 group. The results of immunoblotting also validated that the same ETEC K88 treatment of weaned piglets enhanced the expression of tight junction protein in the intestinal mucosa of the H. illucens addition group. ETEC-induced diarrhea will be reduced by the diet of weaned piglets containing H. illucens larvae, ameliorating the immune performance of piglets. Our results indicates that the optimal dosage of H. illucens replacement in weaned piglets is 4%.